2023
DOI: 10.1002/advs.202300759
|View full text |Cite
|
Sign up to set email alerts
|

eIF3f Mediates SGOC Pathway Reprogramming by Enhancing Deubiquitinating Activity in Colorectal Cancer

Abstract: Numerous studies have demonstrated that individual proteins can moonlight. Eukaryotic Initiation translation factor 3, f subunit (eIF3f) is involved in critical biological functions; however, its role independent of protein translation in regulating colorectal cancer (CRC) is not characterized. Here, it is demonstrated that eIF3f is upregulated in CRC tumor tissues and that both Wnt and EGF signaling pathways are participating in eIF3f's oncogenic impact on targeting phosphoglycerate dehydrogenase (PHGDH) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Our previous study proved that PHGDH expression in CRC cells could be restored by hsa_circ_0062682, which ultimately promoted serine metabolism and tumor growth in CRC[ 32 ]. Likewise, Pan et al [ 33 ] recently revealed that PHGDH can serve as a novel substrate for GSK3β/FBXW7β, and that eIF3f can enhance the serine one-carbon metabolic pathway to promote CRC progression by deubiquitinating PHGDH. In contrast, increased alcohol dehydrogenase 1C was found to reduce serine levels by simultaneously inhibiting the expression of PHGDH, thereby inhibiting the growth, migration, and invasion of CRC cells[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study proved that PHGDH expression in CRC cells could be restored by hsa_circ_0062682, which ultimately promoted serine metabolism and tumor growth in CRC[ 32 ]. Likewise, Pan et al [ 33 ] recently revealed that PHGDH can serve as a novel substrate for GSK3β/FBXW7β, and that eIF3f can enhance the serine one-carbon metabolic pathway to promote CRC progression by deubiquitinating PHGDH. In contrast, increased alcohol dehydrogenase 1C was found to reduce serine levels by simultaneously inhibiting the expression of PHGDH, thereby inhibiting the growth, migration, and invasion of CRC cells[ 34 ].…”
Section: Discussionmentioning
confidence: 99%